ANALISIS PENDAPATAN DAN FAKTOR .YANG .MEMPENGARUHI USAHATANI BAWANG. MERAH PADA MASA PANDEMI (Di Ds. Kalidawir Kec. Kalidawir Kab. Tulungagung) - Nur Aziz Widianto; Yuhanin Zamrodah; palupi Puspitorini (Universitas Islam Balitar, 2022)
The purpose of this study is to find out how important the factors that affect the onion farming business actors in Kalidawir Village are. According to the findings of this study, the difference between income and production costs is how onion farmers make money during the pandemic. Each farmer earns an average of Rp from onion farming.13,009,267. This value indicates that every RP is spent on production. Farmers will receive Rp 7,888,617 per growing season Rp 5,120,650. In addition, factors that affect the income of shallot farming business actors in the Kalidawir Village area. That, except for the variable amount of production, none of the three free variables (variables of age, land area, and cost.production) had a significant negative impact on the increase in the income of the onion farming business. during the pandemic.